Motivations, Barriers and Physical Condition in Adolescents, According To the Stage of Change in Physical Exercise - Planas, Antoni; Reig, Francesc; Palmi, Joan; del Arco, Isabel; Antoni Prat, Joan (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
Through a descriptive and cross-sectional study, a classification is made on the moment of change in physical exercise in adolescents and the relationship with motivations, barriers and physical condition is analyzed in a sample of 379 Spanish young people between 12 and 16 years of age. These evaluations make possible to prepare a basis for an action’s proposal to improve the process of changing habits towards physical exercise. The results show that the majority of the study population (52.2%) is in the Maintenance stage, observing a difference in women (38.3%), and an alarming decrease in physical activity as age increases. The most outstanding motivations are prevention and health, followed by the search for fun and well-being; The most obvious barriers are obligations and lack of time. For this reason, intervention programs should consider these aspects, offering activities compatible with school hours, generating motivational contexts and adapted to the stage in which the subject is.